Minority youth acculturation in third spaces: an ethnography of Arab-Palestinian high school students visiting the Israeli innovation sector. - Diamond, Aurel H. (Journal of Ethnic & Migration Studies)
Processes of acculturation occur when there is a need to reconcile minority identity with the hegemonic majority culture. What acculturation strategies do minority students adopt in social contexts that are not dominated by either the minority or majority cultures? In order to address this question, this paper offers an ethnographic account of three classes of Arab-Palestinian minority high school students aged 15–17 over the course of 21 months in Israel before, during and after participation in a programme designed to increase understanding of and exposure to the innovation sector. I argue that this curricular programming, which exposes students to internationalisation, globalisation and multinationalism, constitutes a 'third space' that is distinct from both the Arab-Palestinian home/family context and the hegemony of Jewish-majority society in Israel. Within this third space, some Arab-Palestinian students adopt strategies of acculturation that are distinct from their strategies in mainstream Israeli society. The opportunity to partially circumvent or leave the context of Israeli society within third spaces facilitates this distinction. The paper accordingly develops a schema that links theories of acculturation to third space theory, and provides empirical examples of how third spaces can facilitate unique strategies of acculturation.